2010
DOI: 10.1051/0004-6361/201014807
|View full text |Cite
|
Sign up to set email alerts
|

Environmental dependence of local luminous infrared galaxies

Abstract: Aims. We study the environmental dependence of local luminous infrared galaxies (LIRGs) and ultraluminous infrared galaxies (ULIRGs) found in the Sloan Digital Sky Survey (SDSS) data. Methods. The LIRG and ULIRG samples are constructed by cross-correlating spectroscopic catalogs of galaxies of the SDSS Data Release 7 and the Infrared Astronomical Satellite Faint Source Catalog. We examine the effects of the large-scale background density (Σ 5 ), galaxy clusters and the nearest neighbor galaxy on the properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 88 publications
10
75
1
Order By: Relevance
“…Although SDSS surveys a huge field, there is some residual incompleteness in dense regions due to fiber collisions (Strauss et al 2002;Park & Hwang 2009;Shen et al 2016). We thus compile missing redshifts from the literature, mainly from NED (for more details, see Hwang et al 2010). In total, we compile 22410 redshifts within < ¢ R 300…”
Section: Comamentioning
confidence: 99%
“…Although SDSS surveys a huge field, there is some residual incompleteness in dense regions due to fiber collisions (Strauss et al 2002;Park & Hwang 2009;Shen et al 2016). We thus compile missing redshifts from the literature, mainly from NED (for more details, see Hwang et al 2010). In total, we compile 22410 redshifts within < ¢ R 300…”
Section: Comamentioning
confidence: 99%
“…The SFRs of galaxies are known to depend strongly on the local density in the sense that spatially averaged SFRs of galaxies or star-forming galaxy fractions decrease as the background density increases in the local universe (e.g., Lewis et al 2002;Gómez et al 2003;Park et al 2007;Lee et al 2010;Hwang et al 2010a). In the high-z universe, some studies found similar results (e.g., Patel et al 2009;Feruglio et al 2010), but there are also hints for an opposite trend (i.e.…”
Section: Fig 6 Same Asmentioning
confidence: 99%
“…Many studies have extensively investigated this enhancement of SFA in paired galaxies Article published by EDP Sciences A60, page 1 of 10 (e.g., Condon et al 1982;Keel et al 1985;Kennicutt et al 1987;Barton et al 2000;Lambas et al 2003;Nikolic et al 2004;Alonso et al 2004;De Propris et al 2005;Geller et al 2006;Woods & Geller 2007;Li et al 2008;Ellison et al 2008;Knapen & James 2009;Perez et al 2009;Park & Choi 2009;Hwang et al 2010a;Xu et al 2010;Darg et al 2010;Patton et al 2011). In summary, the SFA of galaxies seems to strongly depend on the morphology and the mutual separation of galaxies in pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Though galaxies undergoing a starburst event are commonly associated with a late-type morphology (i.e., spiral, irregular, or chaotic), a non-negligible fraction of starbursts are, surprisingly, associated with early-types (Mobasher et al 2004;Poggianti et al 2009;Abramson et al 2013). Additionally, starbursts are observed in hosts that span a wide range of stellar masses (e.g., Lehnert & Heckman 1996;Elbaz et al 2011, Hilton et al 2012Ibar et al 2013), color properties (e.g., Kartaltepe et al 2010b;Kocevski et al 2011a), and environments (e.g., Marcillac et al 2008;Gallazzi et al 2009;Hwang et al 2010a;Lemaux et al 2012;Dressler et al 2013). And though some starbursting populations show morphologies indicative of a recent merging or tidal interactions, others appear primarily as undisturbed, grand-design spirals, with little evidence of recent interactions with their surroundings (see, e.g., Ravindranath et al 2006;Kocevski et al 2011a;Tadhunter et al 2011).…”
Section: Introductionmentioning
confidence: 99%